Building The Management System: Designs on the use of Blended Learning Environment. Issue 1 (February 2021) - Musdalifah, Musdalifah; Baharuddin, Baharuddin; Jabri, Umiyati; Elihami, Elihami; Mustakim, Mustakim
Abstract: This study addressed the role of children in studying education is the use of education system. The goal of this study is to develop the international community-based research approach, which is a characteristic assessment involving non-participating observation, interviews and documentation. This research focuses on the models of teaching materials for training to use the full daily school system. The whole research focuses on the models of instructional media for learning through the use of a full day state education system. The data were analyzed to use a qualitative descriptive tool. The aim of data collection is to define teaching assessment by means of interview, review, assessment, documents and research instruments. Participants included 300 elementary school graduates, namely Sidenreng Rappang Regency, Enrekang Regency, Pinrang Regency, Barru Regency and Parepare City, South Sulawesi, Indonesia. The findings of the study showed no substantial associations between the introduction of a full day public education system, personal development, and a positive mindset. The researcher shall be allowed to examine the research questionnaire identified for this analysis and the field of activity research. On the other hand, the full days public school is substantially successful in the training program for elementary school children. Most of the functionality used in the originality of this research by the research instrument selected for the study are approved and used to understand the impact of mobile-based surveys on the character development to be significant predictors.